A Sociological Analysis of Factors Affecting Job Satisfaction Among Employed Women in District Dir Lower, Khyber Pakhtunkhwa, Pakistan - Adnan Khan; Dr. Bushra Hassan Jan, (Dialogue Social Science Review (DSSR), 2025)
The aim of the current study was to analyze the sociological factors affecting job satisfaction among employed women in district Dir Lower, Khyber Pakhtunkhwa, Pakistan. The nature of the study was quantitative. The data were collected from two union councils i.e. Lajbook and Hayaseri of District Dir Lower. Furthermore, a total of 6 girls’ schools were selected from each union council. A sample of 177 respondents was selected from the target population through a well thought questionnaire. A uni-variate and bi-variate analyzed was conducted by SPSS software. To test the association between dependent and independent variables a Chi-sqaure test was also applied. The study found a significant association (p<0.05) between job satisfaction with social network i.e. role of education in seeking employment, access to employment information and familial support in securing employment. Furthermore, the results also found a significant association (p<0.05) between job satisfaction and the role of education in seeking employment. The study recommends that government should expand access to quality education and vocational training programs for women, especially in rural and underserved areas of KP, provide women in KP with training in digital literacy and access to online job platforms and engage local communities and families in promoting the importance of women's work and the value of their economic contributions.